The Impact of Intellectual Capital on Enhancing Technological Innovation in Palestinian Banks - Abu Ghaben, Ahmed Farooq; Alayan, Ahmed Ismail (The Arab Journal of Administration, 2024)
The aim of the study is to identify the impact of the intellectual capital on enhancing technological innovation in Palestinian banks. To accomplish his study, the researcher prepared a questionnaire as a main tool, and also conducted interviews, as he adopted the descriptive analytical approach. As to the study population, it consists of 200 staff members, employed in Bank of Palestine and Palestine Islamic Bank in the Southern Governorates, who provide direct services to the public. In addition, the researcher used the complete census method, where the number of the distributed questionnaires was, From the targeted population 200, 167 responded to the questionnaire with 83.5% response rate. The most prominent results of the study were as follows: 1- There is a significant relationship between intellectual capital with its different dimensions (human capital, structural capital, and relational capital) and the enhancement of technological innovation in Palestinian banks operating in the Southern Governorates. 2- Intellectual capital’s dimensions (human capital, structural capital, and relational capital) have an influence on the promotion of technological innovation in Palestinian banks operating in the Southern Governorates.